Cabaran Abad 21 Dan Keperluan Amalan Kerohanian Oleh Warga Emas - Muhammad Khairi Mahyuddin; Roslee Ahmad; Atifah Mamat; Awatif Abdul Rahman (Institut Agama Islam Al Mawaddah Warrahmah Kolaka, 2024)
Volume: 1 No: 2